2022
DOI: 10.3390/cells11244052
|View full text |Cite
|
Sign up to set email alerts
|

Plant Plasma Membrane Proton Pump: One Protein with Multiple Functions

Abstract: In plants, the plasma membrane proton pump (PM H+-ATPase) regulates numerous transport-dependent processes such as growth, development, basic physiology, and adaptation to environmental conditions. This review explores the multifunctionality of this enzyme in plant cells. The abundance of several PM H+-ATPase isogenes and their pivotal role in energizing transport in plants have been connected to the phenomena of pleiotropy. The multifunctionality of PM H+-ATPase is a focal point of numerous studies unraveling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 148 publications
1
4
0
Order By: Relevance
“…PM ATPase activity has been reported to be altered by drought in many plant species [ 49 , 50 ]. In our study, PM ATPase activity is significantly reduced by drought stress, a reduction that has been previously reported by other investigators [ 51 , 52 ]. These findings are also in agreement with the results of Mi et al [ 53 ], who showed that Na + , K + -ATPase, and Ca 2+ , Mg 2+ -ATPase activities of winter rapeseed leave cells gradually decreased with increasing drought severity.…”
Section: Discussionsupporting
confidence: 91%
“…PM ATPase activity has been reported to be altered by drought in many plant species [ 49 , 50 ]. In our study, PM ATPase activity is significantly reduced by drought stress, a reduction that has been previously reported by other investigators [ 51 , 52 ]. These findings are also in agreement with the results of Mi et al [ 53 ], who showed that Na + , K + -ATPase, and Ca 2+ , Mg 2+ -ATPase activities of winter rapeseed leave cells gradually decreased with increasing drought severity.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, K + uptake under low K + conditions is promoted by the direct interaction between AHA2 and the receptor-like protein kinase BAK1 (Wang et al, 2022). Since the electrical membrane potential and chemical pH gradient generated by the proton-pumping ATPase AHA2 are essential for the function of the majority of plant PM transporters, it is not surprising that AHA2 is regulated by and interacting with many physiological parameters and protein factors (reviewed by Falhof et al, 2016;Michalak et al, 2022). AHA2 expression is affected by changing nitrate supply (Młodzińska et al, 2015) and phosphorus deficiency (Yuan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In plants, the sodium pump is replaced by a P-type proton pump of similar structure and mechanism, powered by ATP hydrolysis to generate an electrochemical proton gradient that powers transport of ions and substrates across the plasma membrane ( Michalak et al, 2022 ). The plant vacuole is powered by V-type proton ATPases and by a pyrophosphatase-hydrolysis coupled proton pump ( Harrison and Muench, 2018 ).…”
Section: Bioenergetic Myth 2 Atp Use = Energy Consumptionmentioning
confidence: 99%